Louisiana Rambles : Exploring America's Cajun and Creole Heartland - McNulty, Ian, 1973- (Book collections on Project MUSE., 2011)
After Hurricane Katrina laid bare the fragility and environmental peril of south Louisiana, author Ian McNulty set out on a series of daytrips to delve into the area's diverse cultural landscapes. He explored communities staked up and down the Mississippi River, nestled into the teeming bayous, braced along the edge of the Gulf, and planted out on the golden prairie stretching to the west. Louisiana Rambles is his richly evocative guide to those journeys.